Naturally Challenged: Contested Perceptions and Practices in Urban Green Spaces. - (:unkn) unknown (Springer, 2020)
This book aims to understand how the wellbeing benefits of urban green space (UGS) are analysed and valued and why they are interpreted and translated into action or inaction, into ‘success’ and/or ‘failure’. The provision, care and use of natural landscapes in urban settings (e.g. parks, woodland, nature reserves, riverbanks) are under-researched in academia and under-resourced in practice. Our growing knowledge of the benefits of natural urban spaces for wellbeing contrasts with asset management approaches in practice that view public green spaces as liabilities. Why is there a mismatch between what we know about urban green space and what we do in practice? What makes some UGS more ‘successful’ than others? And who decides on this measure of ‘success’ and how is this constituted? This book sets out to answer these and related questions by exploring a range of approaches to designing, planning and managing different natural landscapes in urban settings.
Keywords: Stadtgrün; Stadtnatur; Wohlbefinden; Stadtökologie; Ökosystem; Gesundheit; Stadtbegrünung; Öffentliches Grün; Natürliche Umwelt; Planungspraxis; Freiraumplanung; Grüne Infrastruktur